Investigation and Mitigation of Harmonic Distortion and Parallel Resonance in an Industrial Power System Using ETAP (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Harmonics, primarily generated by non-linear loads, can lead to voltage distortion, equipment overheating, and reduced system efficiency. This project analyzes harmonic distortion in the electrical distribution network of a cement plant using ETAP software. A detailed Single Line Diagram (SLD) was modeled, and harmonic load flow analysis was conducted to evaluate Total Harmonic Distortion (THD) at key bus locations. A frequency scan was performed to identify parallel resonance conditions, which were mitigated by installing series reactors with capacitor banks. Additionally, passive filters were designed to reduce dominant harmonic components and ensure compliance with IEEE 519 standards. The study demonstrates a significant improvement in power quality and highlights ETAP as an effective tool for harmonic analysis and mitigation in industrial systems.